2013
DOI: 10.2174/1874325001307010334
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Shoulder Hemiarthroplasty and Humeral Head Resurfacing: A Review of Current Concepts

Abstract: Since Neer’s early work in the 1950s shoulder arthroplasty has evolved as a treatment option for various glenohumeral joint disorders. Both hemiarthroplasty and total shoulder prostheses have associated problems. This has led to further work with regards to potential resurfacing, with the aim of accurately restoring native proximal humeral anatomy while preserving bone stock for later procedures if required. Hemiarthroplasty remains a valuable treatment option in the low demand patient or in the trauma setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…Compared with stemmed humeral prostheses, there are lower rates of bleeding and fracture because a humeral osteotomy is not performed. 61,62 Additionally, bone stock is preserved for future revisions. Studies have shown improved functional outcomes with resurfacing.…”
Section: Humeral Head Resurfacingmentioning
confidence: 99%
“…Compared with stemmed humeral prostheses, there are lower rates of bleeding and fracture because a humeral osteotomy is not performed. 61,62 Additionally, bone stock is preserved for future revisions. Studies have shown improved functional outcomes with resurfacing.…”
Section: Humeral Head Resurfacingmentioning
confidence: 99%
“…The analysis was performed in order to obtain results about how the artificial design responds to different factors, such as load, type of material, and type of test. The dimensions of the global humeral head implant are assessed based upon the observed variability in humeral head sizes in the normal shoulder [17][18]. The stress and surface deformation analyses were done on the artificial HH using three different biomaterials: Co-Cr alloy, Ni-Ti alloy, and Al-foam (their properties were described previously in Table 1).…”
Section: Design and Development Of 3d Surface Mapping For Artificial mentioning
confidence: 99%
“…Several national registry studies compared patient-reported outcomes between RHA and SHA but no significant differences were observed [38][39][40]. Moreover, a published review comprehensively discussed their indications, clinical assessment, patients' satisfaction and postoperative complications but was restricted to descriptive analysis [41]. To the best of our knowledge, there was no meta-analysis that provided more reliable evidence on this issue.…”
Section: Introductionmentioning
confidence: 99%